Pengaruh Aplikasi Formula Pantoea agglomerans Terhadap Aktivitas Antioksidan dan Kandungan Klorofil Daun Tanaman Strowberi - TRISNA AGUNG PHABIOLA; KHAMDAN KHALIMI (Agrotrop : Journal on Agriculture Science, 2012)
The objectives of this experiment were conducted to evaluate the effectiveness of Pantoeaagglomerans formulations to increase antioxidant activities and chlorophyll content of strawberry plants.P. agglomerans was formulated in the forms of gel and powder. Measurement of peroxidase activitycarried out 7 days after application of P. agglomerans formulations on strawberry plants. The mannerin which the Cohen prosedure suggested by Simon and Rose (1970) and has been modified. Totalchlorophyll content (SPAD unit) was determined with a chlorophyll-meter SPAD-502. Some growthparameters were observed such as plant height, number of leaves, and leaf area. Results of this studyshowed that application of P. agglomerans formulations could increase the peroxidase activity. Peroxidaseactivity on treated plants increased by 47.17% to 50.16% in comparison with un-treated plants. Totalchlorophyll content on treated plants increased by 23.81% to 28.22% in comparison with un-treatedplants. These results suggested that application of P. agglomerans formulations could increase the totalchlorophyll content and antioxidant activity of strawberry plants.